Treatment of loco-regional recurrence of nasopharyngeal carcinoma in a non-endemic area: oncologic outcomes, morbidity, and proposal of a prognostic nomogram - Rampinelli, Vittorio; Ferrari, Marco; Mattavelli, Davide; Bonomo, Pierluigi; Lambertoni, Alessia; Turri-Zanoni, Mario; D’Angelo, Elisa; Alterio, Daniela; Cianchetti, Marco; Vischioni, Barbara; Rosati, Roberta; Tomasoni, Michele; et al. (Frontiers in Oncology, 2023)
Introduction The study assessed outcomes and toxicities of different treatment modalities for local and/or regional recurrent nasopharyngeal carcinoma (NPC) in a non-endemic area. Methods Patients treated with curative intent for recurrent NPC with salvage surgery, photon-based radiotherapy, proton therapy (PT), with or without chemotherapy, at different Italian referral centers between 1998 and 2020 were included. Adverse events and complications were classified according to the Common Terminology Criteria for Adverse Events. Characteristics of the patients, tumors, treatments, and complications are presented along with uni- and multivariate analysis of prognostic factors. A survival predictive nomogram is also provided. Results A total of 140 patients treated from 1998 to 2020 were retrospectively assessed. Cases with lower age, comorbidity rate, stage, and shorter disease-free interval (DFI) preferentially underwent endoscopic surgery. More advanced cases underwent re-irradiation, fairly distributed between photon-based radiotherapy and PT. Age and DFI were independent factors influencing overall survival. No independent prognostic effect of treatment modality was observed. No significant difference in the morbidity profile of treatments was observed, with 40% of patients experiencing at least one adverse event classified as G3 or higher. Conclusion Recurrent NPC in a non-endemic area has dissimilar aspects compared to its endemic counterpart, suggesting the need for further studies that can guide the choice of the best treatment modality.